Learning to adapt & adapting to learn - Using elements of outcome mapping in the ‘Resilient Adolescents in the Syria Crisis’ programme - van Ongevalle, Jan; Kvintradze, Ana; Rennesson, Gaël; Miller, David (Save the Children, 2021)
This learning paper highlights how elements of outcome mapping were used by Save the Children Sweden in a project (2018-2020) that supports adolescents, affected by the Syria crisis, to become more resilient. The paper first outlines how the spheres of influence framework has been applied to develop an actor focused theory of change. It then describes how progress markers, as an alternative to SMART indicators, were formulated to monitor the programme’s results. The paper also outlines how long lists of progress markers were categorised in a more realistic and practical results framework. The paper then continues to elaborate how outcome journals, qualitative data analysis techniques and regular review meetings and reflection workshops were utilised for data collection, for collective learning among programme stakeholders and for informing planning and programme adjustment. Various practical guidelines and tips on how to implement elements of outcome mapping are provided. The final part of the paper explores to what extent outcome mapping was able to foster several key enablers of adaptive programme management and highlights some of the challenges that programme stakeholders faced. Practical recommendations towards the use of outcome mapping in future programmes are also proposed.

Outcome mapping: learning brief - Buell, Stephanie; Malallah, Haneen; Mason, Paige (Briefing Paper, 2020)
Adaptive programmes recognise that certain changes, particularly in behaviours, are complex, non-linear and difficult to measure. This briefing note explores the use of outcome mapping (OM) as a monitoring, evaluation and learning (MEL) approach to track behavioural change and inform adaptation for two programmes: the Pathways to Resilience in Semi-arid Economies (PRISE) research consortium and the Accountability in Tanzania programme (AcT I and AcT II). It discusses the implementation of OM, the ways in which it has enabled adaptation and enabling contexts in order to identify key considerations for MEL specialists and programme managers as they determine whether OM may be the right fit, and how best to use the approach. Key messages OM has a number of different benefits as a MEL approach, including unpacking different uses of information at different levels of programme implementation; helping to develop a common language around progress markers; and going beyond monitoring to inform adaptation throughout implementation. These benefits are important aspects of monitoring, evaluation and learning for adaptive management (MEL4AM), as they provide richer evidence for decision-making at a frequency that could mean real-time learning and change. OM works best when it is embedded throughout the organisation, and as part of programme and organisational culture, rather than tasked to a MEL unit or individual.

A Guide to Participatory Outcome-Focused Monitoring with Most Significant Change, Outcome Harvesting, and Outcome Mapping - Smith, Richard (CARE, 2023)
Audience This guidance is primarily aimed at development and humanitarian professionals who design or manage monitoring and evaluation processes to support design and implementation of qualitative monitoring using Most Significant Change (MSC), Outcome Harvesting (OH), or Outcome Mapping (OM), which are participatory, outcome-focused qualitative methods. Purpose This guidance is a resource to strengthen qualitative monitoring, specifically addressing commonplace gaps or weakness in the monitoring of complex development and humanitarian projects. Importantly, these gaps include: 1. Lack of evidence about unexpected, as well as expected, changes or outcomes, especially during project implementation. 2. Limited documentation about whether and how a project contributed to change. Such information is vital to learning about what worked and how to build on successes. 3. Limited data to inform the review of theories of change, which limits their function and relevance. Addressing these monitoring gaps has the potential to contribute to more informed and effective adaptive management and learning. This guidance can be used to support the design and implementation of monitoring exercises using MSC, OH, and OM. Specifically, it supports users in choosing among MSC, OH, and OM or blending elements from these approaches. Additionally, it provides practical tips and examples - including expertise gained during the two pilot qualitative monitoring activities conducted in Niger and Bangladesh - as well as other publicly available materials. 1. Relevant CARE guidance and tools include: 1. Qualitative Methods Guidance Note for Monitoring, Evaluation and Learning (MEL) at CARE; 2. Outcome Mapping Manual: Development of a monitoring system for the Right to Food project using Outcome Mapping, CARE Nepal; 3. Tipping Point MEL Methods Brief: Outcome Mapping; 4. The Rolling Profile Tool.